Pesquisa operacional aplicada à logística - Monteiro, Elton Andrade (2016)
This research aimed to make an analytical study of the relationship between the Operations Research (OR) and the logistics on a point of view of the organization's improved results of the logistics through the application of the three methods of PO in the processes of Logistics (transportation, raw materials, stock, etc). The main goal is to show that many of the problems faced by the logistics department in an organization can be solved by a simple application of Operations Research, by a competent person for such action.